Evaluation of the role of silicon in alleviating cadmium stress in sorghum - Gökdere, Hazel; Inci, Hava Şeyma; Bilir, Bedriye (Frontiers in Plant Science, 2026)
IntroductionThis experiment was designed to examine the mitigating effects of Si treatment on Cd-exposed sorghum plants and was conducted as a pot experiment.MethodsThe experiment was executed using a factorial design in completely randomized design (CRD), including 3 Cd concentrations (0, 10, and 20 mg kg-1) and 4 Si concentrations (0, 100, 200, and 300 mg kg-1). After 90 days, the plants were harvested, and the Cd, Fe, and Zn concentrations in the plant organs, as well as the morphological characteristics of the plants, were examined.ResultsCadmium accumulated most in the roots compared to other organs of sorghum; roots>stems>leaves=panicle. Si treatments in Cd10 stress reduced Cd concentration in roots and panicles, Fe in stems and panicles, and Zn in roots. Si treatments in Cd20 exposure increased Fe in roots, while Zn decreased in Stems and leaves. Si treatments in Cd exposure increased plant stem diameter, dry root weight, and total plant weight. Regarding the role of Si application in alleviating Cd exposure in sorghum, the Cd10Si300 treatments reduced Cd by 86.6% in panicles, 30.9% in leaves, and 28.9% in stems, while Cd10Si200 treatments reduced Cd concentration in roots by 38% at most. In Cd translocation to panicles, it was observed that the treatment of 300 mg kg-1 Si had a strong potential to inhibit translocation in the presence of about 10 mg kg-1 Cd.DiscussionIn the soils with similar properties and Cd contamination used in this study, the treatment of 300 mg kg-1 Si is considered to be an important concentration to overcome Cd translocation.